Impact of a glutamine-enriched peptide formula on gastrointestinal toxicity and on the interruption of oncologic treatment in patients with adenocarcinoma of the rectum - Salas-Salas, Bárbara Gabriela; Ferrera-Alayón, Laura; Calleja-Fernández, Alicia; Chicas-Sett, Rodolfo; Nogués-Ramia, Eva; Zafra-Martín, Juan; Lloret, Marta (Frontiers in Nutrition, 2024)
BackgroundPatients with rectal cancer may develop gastrointestinal toxicity associated with chemo-radiotherapeutic treatment that conditions their clinical, functional, and nutritional evolution. The aim of the study was to evaluate the efficacy of nutritional supplementation with a glutamine-enriched peptide diet (PD) compared to exclusive dietary advice (DA) on gastrointestinal toxicity, interruption of oncologic treatment, and nutritional evolution in patients with rectal cancer undergoing neoadjuvant treatment.MethodsProspective cohort study with two groups. Patients with rectal cancer in treatment with neoadjuvant chemo-radiotherapy were recruited. One group of patients received nutritional supplementation with PD, and another group received DA exclusively, from the beginning of radiotherapy until the time of surgery. Intestinal toxicity was evaluated with the CTCAE 5.0 scale, functionality with the ECOG scale and nutritional status with GLIM criteria.ResultsFifty-four patients were initially selected, although 51 were finally enrolled: 25 in the PD group and 26 in the DA group. There was a reduction in the risk of diarrhea in the PD group midway through radiotherapy treatment [RR of 0.218 (95% CI = 0.052–0.923)] and at the end of treatment [RR of 0.103 (95% CI = 0.020–0.537)], as well as a reduction in the risk of developing mucositis at the end of treatment [RR of 0.405 (95% CI = 0.280–0.584)]. The use of a PD also decreased treatment interruptions with radiotherapy in stage III patients (0 vs. 15.8%, p = 0.049) and in malnourished patients (0 vs. 18.2%, p = 0.040).ConclusionThe glutamine-enriched peptide diet had a protective effect on the development of diarrhea and mucositis associated with chemo-radiotherapeutic treatment in patients with colorectal cancer under neoadjuvant treatment, as well as the interruption of radiotherapeutic treatment.